The Role of Formal and Informal Socialization in the Creation of a Supply Chain Rational Capital in the Food Industry of Thailand - Natnaporn Aeknarajindawat; Tawee Piyapattana; Sudawan Somjai; Pannamas Aramrueang (International Journal of Supply Chain Management, 2019)
The study is carried out to examine the interrelationship among the capital formation mechanism, formal socialization, informal socialization and the supply chain rational outcome. The study has used the social capital theory to conceptualize interrelationship among the capital formation mechanism, formal socialization, informal socialization and the supply chain rational outcome. The study has employed the SEM-PLS to answer the questions raised in the study. The outcomes obtained for this study have suggested that some context-specific mixture of informal and formal socialization mechanism is needed. The formal structure is needed to form the basis for establishing the mechanism of informal socialization, which could occur after a certain time period. For instance, a senior executive in a food company observed this situation while evaluating potential suppliers for a strategic alliance of a multiyear steel agreement. According to this study, relational capital also facilitates some particular operational metrics in relationship interactions. In addition, the relation capital concept can be used by suppliers and buyers to make relation-specific investments and establish knowledge-sharing relationships for obtaining relational rents. Furthermore, the relational capital must be recognized as a key constituent to foster and maintain relationship performance.  The study is among the pioneering studies on the issues and will be helpful for policymakers and researchers in understanding the issues related to capital formation mechanism, formal socialization, informal socialization and the supply chain rational outcomes in Thai food industry.